Konstruksi Masalah dan Kesenjangan Implementasi Kebijakan Pangan: Studi Kasus Beras Oplosan di Indonesia - Silahudin Silahudin; Akhmad Basuni; Soleh Soleh (The World of Public Administration Journal, 2025)
AbstractThe phenomenon of adulterated rice, uncovered through investigations by the Ministry of Agriculture and mass media, reveals a crisis in Indonesia’s food distribution and regulatory systems. This study aims to examine how the issue of rice adulteration is constructed as a public problem and to identify gaps in the implementation of national food policy. Using a qualitative approach and media content analysis, the article finds that weak quality control, ambiguous labeling standards, and poor law enforcement have enabled irresponsible economic actors to dominate the market. These findings reflect a failure in food distribution governance and the absence of state accountability in ensuring food justice. The article recommends reforming food labeling systems, strengthening the capacity of regulatory institutions, and involving civil society in distribution oversight.   Keywords: Adulterated Rice, Food Policy, Policy Sociology, Problem Construction, Distribution Inequality, Governance   AbstrakFenomena beras oplosan yang terungkap melalui investigasi Kementerian Pertanian dan media massa memperlihatkan realitas krisis dalam sistem distribusi dan pengawasan pangan di Indonesia. Penelitian ini bertujuan untuk mengkaji bagaimana kasus beras oplosan dikonstruksi sebagai masalah publik serta mengidentifikasi kesenjangan dalam implementasi kebijakan pangan nasional. Dengan menggunakan pendekatan kualitatif dan analisis konten media, artikel ini mengungkap bahwa lemahnya pengawasan mutu, ketidakjelasan standar pelabelan, dan lemahnya penegakan hukum telah menciptakan ruang dominasi pasar oleh aktor-aktor ekonomi yang tidak bertanggung jawab. Temuan ini merefleksikan kegagalan tata kelola distribusi pangan dan ketidakhadiran negara dalam menjamin keadilan pangan. Artikel ini menyarankan perlunya reformasi sistem pelabelan pangan, penguatan kapasitas institusi pengawas, serta pelibatan masyarakat sipil dalam pengawasan distribusi.   Kata kunci: Beras Oplosan, Kebijakan Pangan, Sosiologi Kebijakan, Konstruksi Masalah, Ketimpangan Distribusi, Governance